STEM or Humanities? Toward a Balance of Interest Fit - Vaziri, Hoda; Tay, Louis; Parrigon, Scott; Bradburn, Norman M.; Pawelski, James O. (Frontiers in Education, 2019)
Despite a growing number of studies demonstrating the importance of fit between interests and major/career, an increasing discordant rhetoric can be heard emphasizing either STEM or the humanities in education and work. We propose that perception of interest fit is more important than the domain itself per se. Analysis of a national data set of college graduates (N = 8,151) shows that interest fit accounted for more variance in well-being outcomes (work satisfaction, life satisfaction, and financial satisfaction) as compared to STEM or humanities education, and an equivalent amount of variance was found in personal income. Similar trends were found in a second data set of recent college graduates from a Midwest public university (N = 636). Even controlling for ability-related variables and personality, interest fit accounted for more variance in work satisfaction and life satisfaction, an equivalent amount of variance in financial satisfaction, and less variance in personal income. These results reveal that it is important to achieve a balanced approach to education and career guidance where individuals can be directed to careers that capture their interest.